2012
DOI: 10.4236/fns.2012.39171
|View full text |Cite
|
Sign up to set email alerts
|

Organic Crop Management Enhances Chicoric Acid Content in Lettuce

Abstract: L- chicoric acid is a dominant phenolic compound in lettuce (Lactuca sativa L.) and has been shown to accumulate in response to many abiotic stresses and crop management practices. It is a potent inhibitor of human immunodeficiency virus (HIV-1) integrase needed for the replication of this virus and for the productive infection of the host cell. L- chicoric acid has been found to act synergistically in combination with anti-HIV drugs used for treating acquired immuno-deficiency disorder (AIDS). We show in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Cichoric acid and rosmaric acid exist naturally as major phenolic compounds in lettuce (Rajashekar et al, 2012;Becker et al, 2013) and basil (Lee and Schlagel, 2009;Taulavuori et al, 2013), respectively. In accordance with previous studies, cichoric acid was the most abundant phenolic compound found in red leaf lettuce (Table 2) and similarly rosmaric acid in basil (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…Cichoric acid and rosmaric acid exist naturally as major phenolic compounds in lettuce (Rajashekar et al, 2012;Becker et al, 2013) and basil (Lee and Schlagel, 2009;Taulavuori et al, 2013), respectively. In accordance with previous studies, cichoric acid was the most abundant phenolic compound found in red leaf lettuce (Table 2) and similarly rosmaric acid in basil (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…“Verde” zucchini ( Cucurbita pepo L.) samples from a public marketplace contained chicoric acid only when fruit were identified as organically grown (Iswaldi et al, 2013 ). In contrast, growing green leaf lettuce plants grown in conventionally managed field plots had similar chicoric acid concentrations and dry weight as plants grown in 5 year old certified organic plots when plants were fertilized (Rajashekar et al, 2012 ). Interestingly, in the same study, growing plants with organic fertilizer (composted cattle manure and alfalfa hay) decreased chicoric acid concentrations compared to plants grown without additional fertilizer and, plants grown with non-organic fertilizer in non-organic plots had similar chicoric acid concentrations and greater dry weight than plants grown without additional fertilizer.…”
Section: Plant × Growing Environment Interactionsmentioning
confidence: 99%
“…In some research nutrient application rate was also altered with fertilizer form; therefore the effects of fertilizer form on chicoric acid cannot be separated from the differences in nutrient application rates among treatments. Fertilizer additions (organic or non-organic) decreased chicoric acid accumulation in green leaf lettuce (“Baronet”) (Rajashekar et al, 2012 ). Use of a commercial form of cow manure vs. conventional fertilization did not result in chicoric acid differences within chicory leaves, in either water stressed plants or unstressed ones (Heimler et al, 2009 ).…”
Section: Plant × Growing Environment Interactionsmentioning
confidence: 99%
“…Chicoric acid (CA) is a natural dicaffeyltartaric present in a wide variety of edible vegetables and plants such as the Mediterranean vegetables Cichorium intybus L. (chicory) [ 14 ], Echinacea purpurea [ 15 ], Lactuca sativa (iceberg lettuce) [ 16 ], Taraxacum spp. (dandelion) [ 17 ], Ocimum basilicum (basil) [ 18 ], some seagrass such as Cymodocea nodosa [ 19 ], and other plants.…”
Section: Introductionmentioning
confidence: 99%